Watanabe’s Bad Faith in Haruki Murakami’s Norwegian Wood (LITERA KULTURA : Journal of Literary and Cultural Studies, 2016)
Abstrak Analisis eksistensial digunakan dalam studi ini untuk mendiskusikan fenomena keyakinan buruk atau bad faith yang dialami oleh tokoh utama, Watanabe, dalam novel Norwegian Wood karya Haruki Murakami. Analisis ekistensial berfokus pada pengalaman tokoh yang berhubungan dengan sikap tokoh dalam membuat keputusan dan memikul tangungjawab dalam hidupnya. Bad faith yang disebut juga sikap menipu diri sendiri merupakan sikap memungkiri kebebasan dan melimpahkan tanggung jawab dari setiap tindakan pada faktor dari luar diri tokoh. Penelitian ini menggunakan teori eksistensialisme dari Jean Paul Sartre tentang konsep bad faith untuk menganalisa aksi dan emosi tokoh Watanabe dalam novel dan menggunakan metode deskriptif kualitatif untuk menganalisa bagaimana keyakinan buruk Watanabe digambarkan dalam novel. Hasil dari penelitian ini menunjukkan bahwa keyakinan buruk Watanabe diwujudkan dalam tindakan menyangkal kebebasan dan membiarkan dirinya dipengaruhi oleh peristiwa maupun orang-orang tertentu, memainkan peran dan mengabaikan pilihan atau kesempatan yang ada dalam hidupnya. Keyakinan buruk Watanabe bersumber dari rasa takut akan beban tanggungjawab dari kenyataan menyedihakn masa lalunya. Kata Kunci: bad faith, keautentikan, ekistensialisme. Abstract An existential analysis is applied in this study to discuss the phenomenon of bad faith experienced by the main character named Watanabe in Haruki Murakami’s Norwegian Wood. The existential analysis examines the character’s experiences related with his attitude dealing with making decisions and taking responsibility as an authentic human being. Watanabe is regarded as operating the attitude of living in bad faith. Bad faith, also called as self-deception, is an attitude of denying one’s innate freedom and relaying one’s actions on external determination. This study employs Jean Paul Sartre’s concept of bad faith in examining Watanabe’s action and emotion throughout the novel and uses descriptive-qualitative method to analyse how Watanabe’s bad faith is depicted in the novel. The result shows that Watanabe’s bad faith can be seen in the action of having no freedom in his life and letting himself to be determined by certain people and circumstances, playing role and denying choices in his life. Watanabe’s bad faith emerges from the fear of being responsible in facing the pathetic reality of his past. Keywords: bad faith, authenticity, existentialism.